+0  
 
0
28
2
avatar+4269 

Help

NotSoSmart  Nov 21, 2018
 #1
avatar+128 
+1

(1, 1)

(2, 4)

MATHEXPERTISE  Nov 21, 2018
 #2
avatar+92429 
+1

Let's see how ME got that answer

 

Set the equation equal

 

x^2   = 3x - 2      we can subtract 3x - 2 from both sides and we get

 

x^2 - 3x + 2   = 0      factor the left side

 

(x - 2) ( x - 1) = 0

 

Set each factor to 0  and solve for x and we get that

 

x =  2        and y = x^2    =   4

x = 1         and y = x^2   =    1

 

So....as ME found    (2, 4)   and ( 1, 1)

 

 

cool cool cool

CPhill  Nov 21, 2018

11 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.